Analisis Analisis Kerusakan Jalan Menggunakan Metode Pavement Condition Index Pada Ruas Jalan Purwogondo – Teluk - Cawisdi, Cawisdi; Hidayati, Nor; Saputro, Yayan Adi; Mushthofa (Jurnal Civil Engineering Study, 2024)
The Purwogondo - Teluk road section has various problems on this road section, such as holes in the road which cause water to pool when it rains, bumpy roads, cracked roads which make drivers uncomfortable when crossing the road, as well as triggers for traffic incidents. . The road condition assessment used in this research is the Pavement Condition Index (PCI) method. The analysis produces the following surface damage percentages: Very Good 27.3%, Good 9.1%, fair 27.3%, poor 27.3%, very poor 9.1%, average PCI value for the entire road is 51, 1 The PCI value indicates that the road surface is in Fair condition.